(3CbGdje GdJYGdjes - (3eMeO Hf CMeO Hf Ndjd Hf SYGOI GdNhjj, TgGH GdOjf, CHh YHO Gddg,J (B693 (3g` s
(3ChdgG (B:s
(3aUd EYde HCf GdUdGI bGFeI hTQjYI KHJI aQVjJgeG HGdcJGH hGdSfI s
(3BNQgG (B:s
(3hfYe Gdhcjd hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B324 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B258s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B134s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(383) s
Keywords: (3Yde GdaQGFVs